Characteristics of Chicken Liver and Anchovy (Stolephorus indicus) Composite Powder to Prevent Stunting - Nawasari Indah Putri Sejati; Endang Sri Wahyuni; Bertalina Bertalina; Dina Fithriyani (Poltekkes Kemenkes Tanjung Karang, 2026)
Stunting remains a major public health problem in Indonesia, with prevalence still exceeding national targets. Inadequate intake of high-quality animal protein during the first 1,000 days of life is a key contributing factor. Chicken liver and anchovies are affordable local sources of animal protein; however, their fresh forms are highly perishable. Powdered chicken liver and anchovies offer several advantages, including extended shelf life, greater storage practicality, and easier distribution. This study aimed to evaluate the physical, chemical, and sensory characteristics of chicken liver and anchovy composite powder stored for 4–6 weeks. An experimental study using a completely randomized design was conducted with three composite powder formulations: F1 (75% chicken liver:25% anchovy), F2 (50:50), and F3 (25:75). Physical properties (Hunter L*, a*, b*), proximate composition, and sensory characteristics were analyzed before and after storage. Data were analyzed using two-way repeated-measures ANOVA, LMM, and non-parametric tests (α=0.05). Results showed that formulation significantly affected color, texture, and proximate composition. Higher anchovy proportions increased brightness and smoothness. Storage influenced color intensity and aroma in certain formulations but did not affect texture stability. All formulations exhibited low moisture content (<10%) and high protein content (>60%). Protein levels remained stable after storage, while moisture, lipid, and carbohydrate contents were affected. Formula F3 consistently demonstrated superior nutritional and physical stability. With its extended shelf life and favorable nutritional value, the composite powder made from chicken liver and anchovies is expected to serve as a major protein source for stunting intervention, particularly in remote and underserved areas.